EVALUACIÓN FINANCIERA EN LA EMPRESA RAM SYSTEMS DE LA CIUDAD DE LOJA, PERIODO 2013 - ALVAREZ ACHI, KATHERINE STEFANÍA (2016)
The thesis entitled "FINANCIAL EVALUATION IN THE COMPANY" RAM SYSTEMS "CITY OF LOJA, PERIOD 2013" was made to comply with the pre-opt the degree of Engineer in Accounting and Auditing, CPA, National University requirement Loja, adjusting in this way the current Academic Regulations Regime. It was further developed based on the overall goal: Making a Financial Evaluation Systems in the company Ram city of Loja, 2013 period in order to determine their economic and financial situation; being an ideal tool for improving financial management, given the same performance under the following specific objectives. Will determine the financial structure of the company for the period specified in order to meet working capital was developed by applying the vertical analysis to determine the actual economic and financial situation of the company where the percentage level of participation was determined for each one of the items in this economic period. Apply financial reasons as liquidity, turnover, debt and profitability; applicable to this type of entity, was made based on the financial statements, allowing to determine the efficiency and effectiveness of activities performed by administrative part of this entity, they were plotted and interpreted. 6 Use the Index Value Added EVA, in order to know if the net income is sufficient to cover the obligations generated appropriations made and the owner's expectations, based on measurable values, which are presented in the financial statements as State Balance Sheet and Income Statement, being considered a powerful tool that allows to know if a company creates or destroys value to its owner. The methodology helped determine the rate of return on equity denotes a representative on behalf of the enterprise value of 8.01, which means that the owner obtained a work its investment performance and profitability of assets with a value 3.95% of this value is favorable for the company, since the return on assets is efficient. Technically determine the feasibility of investment through financial indicators, achieving obtain a Net Present Value of $ 245.345,77; Internal Rate of Return 30,18%; Capital Recovery Period states that the investment will be recovered in 1 yr 7 months 21 días; Relationship Cost - Benefit 2.04 cents. And Sensitivity Analysis with increased costs, the sensitivity coefficient is 0.9913257; where it is determined that can withstand an increase of 81,52% on estimated cost, in terms of declining revenues sensitivity coefficient is 0.9913257; indicating that it can withstand a drop of 39,30% in estimated revenue. 7 It is recommended to the company Ram Systems to realize at least once a year realizes Financial Evaluation since with the obtained results it will allow to his owner to know the economic and financial structure of each one of his items and with this sustenance adopt also the decisions and corrective opportune actions, for the improvement of the operational activities - financial.